2016
DOI: 10.1002/jccs.201500335
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hexagonal Boron Nitride Nanosheets by Using a Simple Thermal Exfoliation Process

Abstract: A simple and inexpensive method to exfoliate boron nitride powder to form boron nitride nanosheets (BNNSs) with few layers was achieved by using a physically thermal process. The obtained BNNSs were characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), IR spectroscopy, and Raman spectroscopy. The size distribution of the sheets and average sheet size is in the range of 80-380 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
(16 reference statements)
3
9
0
Order By: Relevance
“…Finally, the subsequent suspension was kept for conducting other measurements, like structural and morphological investigations, or it was dried to acquire clean BNNSs. 125 …”
Section: Exfoliationmentioning
confidence: 99%
“…Finally, the subsequent suspension was kept for conducting other measurements, like structural and morphological investigations, or it was dried to acquire clean BNNSs. 125 …”
Section: Exfoliationmentioning
confidence: 99%
“…[113] Methods for preparing BN NSs have been established, for instance, CVD, chemical exfoliation, and thermale xfoliation. [112,114] Owing to the sp 2 -hybridization nature of carbon,the edges of h-BNa re endowed with high chemicalactivity and reduced binding energy.T hus, h-BN is an excellent building scaffold for variousf unctional materials. [112,115] Investigations into the antibacterial activity of h-BN-based nanomaterials are in the initial stages.…”
Section: Nitride-based Antibacterial Nanomaterialsmentioning
confidence: 99%
“…23 Consequently, several techniques have been developed to exfoliate bulk hBN to a single or few-layered hBNNs, including but not limited to mechanical cleavage, 20,35 solvent assisted sonication, 36,37 chemical vapor deposition, 20,38,39 and thermal exfoliation. 40 Exfoliation of hBN is very challenging because of the electronegativity difference between nitrogen and boron. As a result, most of the above exfoliation methods are inefficient and produce low yield, making them costly for large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, most of the above exfoliation methods are inefficient and produce low yield, making them costly for large-scale production. 35,40 The ball milling (BM) technique is the easiest and efficient method for hBN exfoliation. 41,42 Ding et al 41 reported a remarkably high yield reaching up to 98% of hBN nanosheets synthesized by the BM method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation